Human Rights and Islamic Law Discourse: The Epistemological Construction of Abul A’la Al-Maududi, Abdullahi Ahmed An-Naim, and Mashood A. Baderin - Siti Rohmah; Moh Anas Kholish; Andi Muhammad Galib (Justicia Islamica, 2022)
This study aims to analyze the epistemological construction of human rights from the orthodox perspective of Al-Maududi, the liberalism perspective of An-Na'im, and the moderatism perspective of Baderin. This study uses library research with a descriptive-qualitative approach. This study shows that the presence of Al-Maududi's human rights orthodoxy seeks to campaign that the concept of human rights owned by Islam is far more humanistic than the ones campaigned for and standardized by the Western. On the other hand, the presence of liberalism belief moderated by Abdullahi Ahmad An-Na'im strives to fight for Islamic human rights, which can comply with the human rights standards of the Western. The standardization of An-Na'im's liberalism departs from the view that human beings are the measure of everything. Therefore, human rights liberalism is anthropocentric and secular. In the middle of those two different points of view about human rights, Mashood A. Baderin tried to harmoniously mediate Islam and human rights. For Baderin, instead of making those two piles contradict, they should be synergized. Theoretically and practically, this article offers a discourse between the dialectical discourse of Islamic and Western human rights.